Multiple procedure outcomes for nonparoxysmal atrial fibrillation: Left atrial posterior wall isolation versus stepwise ablation. (18th October 2020) - Barbhaiya, Chirag R.; Knotts, Robert J.; Beccarino, Nicholas; Vargas‐Pelaez, Alvaro F.; Jankelson, Lior; Bernstein, Scott; Park, David; Holmes, Douglas; Aizer, Anthony; Chinitz, Larry A.
Abstract: Objective: To compare multiple‐procedure catheter ablation outcomes of a stepwise approach versus left atrial posterior wall isolation (LA PWI) in patients undergoing nonparoxysmal atrial fibrillation (NPAF) ablation. Background: Unfavorable outcomes for stepwise ablation of NPAF in large clinical trials may be attributable to proarrhythmic effects of incomplete ablation lines. It is unknown if a more extensive initial ablation strategy results in improved outcomes following multiple ablation procedures. Methods: Two hundred twenty two consecutive patients with NPAF underwent first‐time ablation using a contact‐force sensing ablation catheter utilizing either a stepwise (Group 1, n  = 111) or LA PWI (Group 2, n  = 111) approach. The duration of follow‐up was 36 months. The primary endpoint was freedom from atrial arrhythmia >30 s. Secondary endpoints were freedom from persistent arrhythmia, repeat ablation, and recurrent arrhythmia after repeat ablation. Results: There was similar freedom from atrial arrhythmias after index ablation for both stepwise and LA PWI groups at 36 months (60% vs. 69%, p  = .1). The stepwise group was more likely to present with persistent recurrent arrhythmia (29% vs. 14%, p  = .005) and more likely to undergo second catheter ablation (32% vs. 12%, p  < .001) compared to LA PWI patients. Recurrent arrhythmia after repeat ablation was more likely in the stepwise group compared to the LA PWI group (15% vs. 4%, p  = .003). Conclusions: Compared to a stepwise approach, LA PWI for patients with NPAF resulted in a similar incidence of any atrial arrhythmia, lower incidence of persistent arrhythmia, and fewer repeat ablations. Results for repeat ablation were not improved with a more extensive initial approach.